Application of Six Sigma methodology in a small-scale foundry industry. Issue 2 (27th May 2014) - Gijo, E.V.; Bhat, Shreeranga; Jnanesh, N.A.
Abstract : Purpose: – The purpose of this article is to illustrate how the Six Sigma methodology was applied to a small-scale foundry industry to reduce the rejections and rework in one of its processes. Design/methodology/approach: – The research reported in this paper is based on a case study carried out in an industry using the Six Sigma Define-Measure-Analyze-Improve-Control (DMAIC) approach and its application in improving the leaf spring manufacturing process of a foundry shop. Findings: – The root causes for the problem of rejection and rework were identified through data-based analysis at different stages in the project. The process parameters were optimized and measures for sustainability of the results were incorporated in the process. As a result of this study, the overall rejection was reduced from 48.33 to 0.79 per cent, which was a remarkable achievement for this small-scale industry. This was leading to improvement in on-time delivery to the customer. The finance department of the company estimated the annualized savings due to the reduction in rejection and was to the tune of USD8, 000 per year. Research limitations/implications: – The paper is based on a single case study executed in a company, and hence, there is limitation in generalizing the specific results from the study. However, the approach adopted and the learning from this study can be generalized. Originality/value: – This article illustrates the step-by-step application of Six Sigma DMAIC methodology in a small-scale foundry industry to solve an age-old problem in the organization. Thus, this article will be helpful for those professionals who are interested in implementing Six Sigma to such industries.